OXYTOCIN MASSAGE TRAINING IN FAMILY MOTHER POSTPARTUM IN GENERAL HOSPITAL CENTER dr. SOERADJI TIRTONEGORO KLATEN - Paryono . (STIKES DUTAGAMA KLATEN, 2013)
Background: Breast milk is the best food for baby in early life. To prevent declining milk production an attempt to stimulate the hormone prolactin and oxytocin by breast care, early breastfeeding and oxytocin massage. Oxytocin massage stimulates the hypothalamic in the pituitary gland so myoepithelial cells in the alveoli contracts and stimulates oxytocin thus help prepare for milk production. Oxytocin massage can be be done with the help of the nearest person of postpartum women or family from postpartum women. However, the lack of knowledge about oxytocin massage from the family of postpartum women causes the need for information about oxytocin massage to the families of postpartum women. In order for information about oxytocin massage is easier to deliver then an effort to conduct the oxytocin massage training is done to the family of postpartum women.Goal to know the difference of oxytocin massage skill before and after the training is given to the family of postpartum women in the General Hospital Center dr. Soeradji Tirtonegoro Klaten. Method: this is a quasi experiment research. The research design is one group pretest posttest. The population used in the research was the postpartum women whom were hospitalized in Melati I ward, RSUP dr. Soeradji Tirtonegoro Klaten. The sample was taken from 30 postpartum women whom were given oxytocin massage training. The method of data collection was by conducting oxytocin massage skill and observation. The data was treated based on the univariant analysis with central tendency and bivariant analysis with Paired Sample t-test.Result the analysis of univariant shows that on the average, oxytocin massage skill on postpartum women before having the training is 2.2 and after having the training it is 16.6. The analysis of bivariant shows that t test score is around -17.124 < t table 2.045 on Paired Sample t-test. It shows that Ho is rejected and Ha is accepted, so there is a positive difference in the oxytocin massage skill before and after the training is given to the postpartum women. Conclusion : The training intensifies oxytocin massage skill to the postpartum women.